Metabolism Supports Macrophage Activation - Langston, P. Kent; Shibata, Munehiko; Horng, Tiffany (Frontiers in Immunology, 2017)
Macrophages are found in most tissues of the body, where they have tissue- and context-dependent roles in maintaining homeostasis as well as coordinating adaptive responses to a variety of stresses. Their capacity for specialized functions is controlled by polarizing signals, which activate (or polarize) macrophages by upregulating transcriptional programs that encode distinct effector functions. An important conceptual advance in the field of macrophage biology, emerging from recent studies, is that macrophage activation is critically supported by metabolic shifts. Metabolic shifts fuel multiple aspects of macrophage activation, and preventing these shifts impairs appropriate activation. These findings raise the exciting possibility that macrophage functions in various contexts could be regulated by manipulating their metabolism. Here we review the rapidly evolving field of macrophage metabolism, discussing how polarizing signals trigger metabolic shifts and how these shifts enable appropriate activation and sustain effector activities. We also discuss recent studies indicating that the mitochondria are central hubs in inflammatory macrophage activation.